Bentuk Keterlibatan Orang Tua pada Masa Transisi Anak ke Sekolah Dasar - Oktavia, Citrawanti (UIN Sultan Maulana Hasanudin Banten, 2026)
This study originates from the importance of parents’ roles in supporting children’s readiness to enter primary school. Parental involvement is a key factor because school readiness is influenced not only by academic abilities but also by social, emotional, and independence skills formed through interactions at home. This research employs a descriptive qualitative approach involving 129 parents of children aged 5–7 who are in the transition to primary school. Data were collected through open-ended interviews and analyzed using thematic analysis. The results reveal six main forms of parental involvement: accompanying learning (81.4%), fostering independence (54.3%), establishing daily routines (8.5%), religious routines (3.1%), sensory–motor activities (1.6%), and gadget time regulation (0.8%). Based on involvement frequency, the majority of parents (72 respondents) spent more than one hour preparing their children for school readiness. These findings highlight the need to strengthen collaboration between early childhood education institutions and families to support children’s holistic development.